2016
DOI: 10.1007/s11626-016-0099-9
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor 1 regulation of proliferation and differentiation of Xenopus laevis myogenic cells in vitro

Abstract: To understand the mechanism of muscle remodeling during Xenopus laevis metamorphosis, we examined the in vitro effect of insulin-like growth factor 1 (IGF-1) on growth and differentiation of three different-fate myogenic cell populations: tadpole tail, tadpole dorsal, and young adult leg muscle. IGF-1 promoted growth and differentiation of both tail and leg myogenic cells only under conditions where these cells could proliferate. Inhibition of cell proliferation by DNA synthesis inhibitor cytosine arabinoside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…It has been well documented that PI3K/AKT is a crucial signaling pathway to promote myogenesis and induce muscle hypertrophy [ 33 , 34 ]. IGF1 is a stimulator of PI3K/AKT signaling during muscle differentiation [ 35 ]. In our study, administration of 75 nM IGF1 recombinant protein totally reversed the inhibitory effects of miR-106a-5p.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well documented that PI3K/AKT is a crucial signaling pathway to promote myogenesis and induce muscle hypertrophy [ 33 , 34 ]. IGF1 is a stimulator of PI3K/AKT signaling during muscle differentiation [ 35 ]. In our study, administration of 75 nM IGF1 recombinant protein totally reversed the inhibitory effects of miR-106a-5p.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, integrin striated muscle-specific integrin β1-deficient C57Bl6/J mice exhibit decreased in AKT Ser-473 phosphorylation, glucose uptake, and glycogen synthesis, supporting the role between integrin and insulin signaling in SM [44,45]. Other ECM components such as proteoglycans [46,47], fibronectin [48,49], hepatocyte growth factor (HGF) [50,51], epidermal growth factor (EGF) [52,53], insulin-like growth factor(IGF)-1 [54,55], IGF-2 [56,57], and MMPs [58,59], among others, play crucial roles in myogenesis and adipogenesis. Hence, understanding the inter-tissue connection between WAT and SM in some common genes implicated in ECM remodeling could help to develop strategies against the metabolic disturbances in obesity.…”
Section: Current Evidence Of Adipose and Sm Ecm Remodeling In Obesitymentioning
confidence: 85%
“…Our study showed that the addition of SC79 alleviated the differentiation of GCPMt and the protein expressions of MyoG and MyHC in grass carp with OTA inhibition. This was consistent with research on C2C12: the addition of SC79 increased high glucose-inhibited myotube formation and protein expressions of MyoD and MyoG, while the addition of AKT inhibitors was the opposite, indicating that AKT promotes myogenic differentiation in C2C12 cells . The addition of AKT inhibitors blocked taurine deoxycholic acid from improving glucocorticoid-induced inhibition of myotube differentiation index, MyoG, and MHC expressions .…”
Section: Discussionmentioning
confidence: 99%
“…This was consistent with research on C2C12: the addition of SC79 increased high glucose-inhibited myotube formation and protein expressions of MyoD and MyoG, while the addition of AKT inhibitors was the opposite, indicating that AKT promotes myogenic differentiation in C2C12 cells. 68 The addition of AKT inhibitors blocked taurine deoxycholic acid from improving glucocorticoid-induced inhibition of myotube differentiation index, MyoG, and MHC expressions. 69 The above results indicate that OTA inhibited GCPMs differentiation and fusion mainly by inhibiting the AKT signaling pathway.…”
Section: Ferroptosismentioning
confidence: 99%